Castor oil-based stretchable and biodegradable triboelectric nanogenerators (CO-TENGs) for powering in-vivo wearable devices - Chay, Jie Cheng (Nanyang Technological University, 2020)
Recently, materials selection and device innovations in the area of Triboelectric Nanogenerators (TENGs), working on coupled triboelectrification effect and electrostatic induction, have been widely explored. Particularly for application in in-vivo wearables and implantations; fabrication of biodegradable, biocompatible, and stretchable device, yet cost-effective with high performing triboelectric outputs, remained unseen in most designs. Here, we propose a Castor Oil-based TENG, also known as CO-TENG, for possible application in in-vivo energy harvesting. The use of castor oil allows the possibilities of chemical modifications to achieve desired biodegradable and stretchable films through polycondensation. The vegetable oil itself is safe and biocompatible in its natural form, yet abundant for large-scale production. CO-TENGs were derived from esterification between castor oil and citric acid, to form a biodegradable branched copolyester. Coupled with aliphatic and aromatic diol compounds, such as 1,10-decanediol, 1,12-dodecanediol, and even resorcinol, as crosslinkers to expand the material properties. Overall, all proposed films were deemed biodegradable through hydrolytic mechanism. Physical, thermal, and mechanical properties were determined using various characterization tools. Likewise, in light of the biological interactions required for in-vivo applications, the context of biocompatibility was studied preliminarily through live-dead cell viability assay. From our preliminary studies, the CO-based TENGs showed potential to be further developed for the application intended.